The Need to Study Ahmad Yassaviy in the 21st Century. (Texas Journal of Philology, Culture and History, 2024)
This scientific article analyzes the positive impact of the study of didactic-educational, instructive teachings and teachings of the Sheikh of Turkestan Ahmad Yassaviy on the spirituality of the youth of the XXI century.